Clonal variations in seed characters and germination in Hevea brasiliensis - Ngon, René Menoh A; Ehabe, Eugene Ejolle; Njukeng, Jetro Nkengafac (Journal of Plantation Crops, 2022)
The principal form of dissemination for most plant species is seeds, an important source of biodiversity conservation. For rubber plantations, seeds are the initial material for seedling production. In Cameroon, there is limited information related to clonal seed characterisation and early growth performance. This study sorts to characterise Hevea brasiliensis seeds from GT 1, PR 107, PB 217, PB 235, and PB 260 clones and evaluate the germination rate and seedling early growth characteristics to enable planning for nursery management. Clone GT 1 had the highest seed length (3.98 cm), seed kernel weight (3.4 g) and total seed weight (4.75 g). Clone PB 235 had the heaviest shell (1.96 g). There was no significant correlation between seed size, germination percentage and early seedling growth for the different clones. Clone PR 107 had the lowest per cent seed germination, with just 55 per cent of its seed germinating after two weeks, whereas clone PB 217 had the highest seed germination (92.5%). Seedling height, seed germination percentage and shell weight were significantly correlated. The results of this study provide some useful information for rubber nursery managers.